2018
DOI: 10.18832/kp201802
|View full text |Cite
|
Sign up to set email alerts
|

3-MCPD Process Contaminant in Malt

Abstract: Mikulíková, R., Svoboda, Z., Benešová, K., Běláková, S., 2018: 3-MCPD process contaminant in malt. Kvasny Prum. 64(1): 6-9 3-MCPD (3-chloropropane-1,2-diol) is a process contaminant formed during food processing, namely protein hydrolysis. This substance can also occur in a number of foods produced without hydrolysis, e.g. thermally processed cereals (malt, bakery products). Precursors of 3 -MCPD may be endogenous lipids of cereals and chloride ions. 3-MCPD is classifi ed as a possible human carcinogen for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, it should be noted that the DE estimates are based on the established assumptions, uncertainties, variabilities, and the data gathered in this study. In addition, it is also important to note that there are other potential sources of 3-MCPD such as edible oils and fats, bread crust, toast bread, doughnuts, crisps, roasted coffees, meat and meat products, potato and potato products, bakery products, and smoked products (Baer et al 2010;Jedrkiewicz et al 2016;IFST 2018;Mikulikova et al 2018). It is suggested that a total diet study be conducted to ascertain the actual DE of Filipinos to 3-MCPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the DE estimates are based on the established assumptions, uncertainties, variabilities, and the data gathered in this study. In addition, it is also important to note that there are other potential sources of 3-MCPD such as edible oils and fats, bread crust, toast bread, doughnuts, crisps, roasted coffees, meat and meat products, potato and potato products, bakery products, and smoked products (Baer et al 2010;Jedrkiewicz et al 2016;IFST 2018;Mikulikova et al 2018). It is suggested that a total diet study be conducted to ascertain the actual DE of Filipinos to 3-MCPD.…”
Section: Discussionmentioning
confidence: 99%
“…Chocolates (122–1254 μg/kg) and black malt (55–95 μg/kg) were reported to be exposed to 3-MCPD esters. However, pale malts and Korea doenjang and some other snacks were not detected for 3-MCPD. Considering the wide consumptions of oil and oil-contented foodstuffs, studies about thermal-processing-mediated 3-MCPD ester exposures still needed focus.…”
Section: Recent Occurrences In Foodstuffsmentioning
confidence: 99%
“…26 3-MCPD esters were not only exposed to edible oils or oilrelated foods but could also be formed in other foods containing a high level of fat. Chocolates 5 (122−1254 μg/kg) and black malt 27 (55−95 μg/kg) were reported to be exposed to 3-MCPD esters. However, pale malts 27 and Korea doenjang and some other snacks 28 were not detected for 3-MCPD.…”
Section: ■ Recent Occurrences In Foodstuffsmentioning
confidence: 99%